PROBLEMS OF ENVIRONMENTAL POLLUTION DURING OIL REFINING (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In this paper, the effects of oil and oil products on the ecosystem are considered, soil -contaminated with oil products, accidents, accompanied by the release or threat of the release of chemically hazardous substances (HOOV) as a result of explosions that lead to the destruction of technological networks and engineering structures. In addition, tasks in modern conditions are given that minimize undesirable consequences, rationally using natural conditions.